Agency Problem and Its Enforcement In Funding Mudharabah: Study of Baitul Maal wa Tamwil Usaha Gabungan Terpadu Sidogiri, Malang Branch - Multifiah, Multifiah; Manzilati, Asfi; Hurriati, Laili (International Journal of Social and Local Economic Governance, 2015)
This research aims to: (1) Find out the mechanism of funding mudharabah on BMT UGT Sidogiri, Malang branch. (2) Analyze the emergence of agency and its enforcement in funding mudharabah on BMT UGT Sidogiri Malang branch. Qualitative approach was used in this research method using a case study. Research findings show that: (1) There is no appropriateness of mechanism application of shared profit in terms of its requirement and its payment related to its decision of shared profit as it does not conform to DSN-MUI’s fatwa and concept as well as sharia economist’s opinion. (2) The presence of agency issue which is adverse selection encountered by BMT UGT as it is related to customer’s character which is unpredictable as well as the presence of moral hazard in the form of unconformity of financial use available in contract. This results from BMT’s incapability of doing intensive watch. (3) The enforcement already performed was by monitoring via direct interaction and giving intensives in the form of limitation decided by BMT UGT such as a long term restriction and the amount of funding.Keywords: theory of agency, enforcement, mudharabah, BMT